Homogenization of compressible fluid flow in porous media with interfacial flow barrier (Archives of Mechanics - Test, 1999)
This work is concerned with modelling compressible fluid flow in a composite porous medium with interfacial flow barrier. The macroscopic behaviour and the effective permeability are obtained by homogenization, i.e. by upscaling the description at the heterogeneity scale. Five distinct macroscopic models are derived that relate to five relative orders of magnitude of the interfacial conductance with respect to the permeabilities of the constituents.